Entrare al lavoro nelle città dell’Europa preindustriale. Corporazioni e lavoro libero tra teoria e prassi. - Mocarelli, Luca (OS. Opificio della Storia, 2020)
The contribution deals with a very relevant issue in the framework of the historiographical revision of the role of the guilds in early modern Europe that has occurred over the past twenty years We refer to the apprenticeship and the role it played in the transmission of know-how and technological knowledge. The contribution looks at the Italian experience, first of all by exploiting the research carried out by the dozens of scholars involved in two Prin. A collective work which led to the collection of data regarding more than 1,100 Italian guilds. Secondly it widens the perspective highlighting the fact that many works were carried out outside the guilds framework, in order to offer a more realistic reconstruction of apprenticeship in early modern period.